The Diffracting Light in Contemporary Theatre. (3rd July 2020) - Chan, Amy
Abstract : Light in theatre has long remained in a linear reflective relationship with performance and spectators, which is governed by the conceptual framework of dramatic theatre. It is subordinated to texts, representational, illusionary and atmospheric. The double-slit diffraction experiment reveals the paradoxical wave-particle duality property of light other than its linearity. The diffraction patterns exposed not only leads the way to quantum physics but also open up their potentialities in reimagining the conceptual frameworks of light and theatre. By re-turning to three original cross-disciplinary light-theatre-installation works through the concept and diffractive methodology proposed by Karen Barad, I examine the diffraction patterns created within and beyond the works to reconfigure the aesthetics of light in contemporary theatre. Light sets out from the concept of postdramatic theatre and its critical questioning of dramatic theatre to diffract and entangle with medicine, theatre, music, space, time, life, death, Cantonese opera, Hong Kong, world and spectators. Light destabilizes and diffracts the space-time of medicine-theatre, cut together-apart the infinite possibilities within a light-installation, troubles the space-time-matter and re-visit the entanglement of tradition-contemporaneity-fiction-reality-Hong Kong-world in a light-Cantonese opera performance. The on-going intra-actions within and beyond light in the three works re-turn and reconfigure the aesthetics of light, theatre and installation. They also call for the responsibility and response-ability of light and theatre inclusive of spectators, and the re-imagination of the ethico-political in the theatre-world.